Pemodelan matematis reaksi oksidasi katalitik fero sulfat menjadi feri sulfat - Takdir Syarif; Andiyan Yuwono (Jurnal Rekayasa Proses, 2008)
Iron was dissolved in a sulfuric acid to form a concentrated ferrous sulphate (FeSO4) solution. This research was conducted to form ferric sulfate by catalytic oxidation of ferrous sulfate using manganese dioxide as catalyst. The system was a three-phase heterogeneous reaction with a quite complex kinetics The present study aimed at developing a mathematical modeling of three-phase reaction kinetics that involved gas, liquid and solid. Oxidation was undertaken in an isothermal isobaric condition in a three-neck flask reactor. The experiment was conducted in a temperature range of 323 to 353 K with a catalyst concentration of 1.7 g/L. The results indicated that the reaction kinetics could be approached with a quasi steady state model and the chemical reaction on the catalyst surface was the determining step.